Financial Market Fragilities in Latin America : From Banking Crisis Resolution to Current Policy Challenges - Weisbrod, Steven (IMF Working Papers; Working Paper ;, 1994)
This paper has two objectives: first, by reviewing the recent experience of five Latin American countries with the restructuring of their financial sectors, it derives lessons regarding the most effective ways to resolve banking difficulties in developing countries. Second, the paper analyzes current policy challenges associated with the health of financial systems in Latin America, including: (a) designing policies to respond to the recent large inflows of capital that maintain long-run macroeconomic stability and healthy financial systems; and (b) evaluating the impact of capital markets competition on the soundness of banking systems.